2002
DOI: 10.1172/jci0213605
|View full text |Cite
|
Sign up to set email alerts
|

Multiple immuno-regulatory defects in type-1 diabetes

Abstract: Susceptibility to immune-mediated diabetes (IMD) in humans and NOD mice involves their inherently defective T cell immunoregulatory abilities. We have followed natural killer (NK) T cell numbers in patients with IMD, both by flow cytometry using mAbs to the characteristic junctions found in the T cell receptors of this cell subtype, and by semiquantitative RT-PCR for the corresponding transcripts. Both before and after clinical onset, the representation of these cells in patients' PBMCs is reduced. We also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
433
6
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(472 citation statements)
references
References 67 publications
26
433
6
7
Order By: Relevance
“…A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24]. The impact of CD4 + CD25 high T cells in immunoregulation is critically supported by observations of Bennett et al [37] who demonstrated that mutations of Foxp3, a transcription factor which is essential for CD4 + CD25 high T cell function, cause the immune dysregulation, polyendocrinopathy, enteropathy, and X-linked syndrome (IPEX).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24]. The impact of CD4 + CD25 high T cells in immunoregulation is critically supported by observations of Bennett et al [37] who demonstrated that mutations of Foxp3, a transcription factor which is essential for CD4 + CD25 high T cell function, cause the immune dysregulation, polyendocrinopathy, enteropathy, and X-linked syndrome (IPEX).…”
Section: Discussionmentioning
confidence: 93%
“…Implication of T reg in human autoimmune disease is currently under intense investigation. Either reduced numbers or suppressive capacities of T reg were recently reported in patients affected by type-1 diabetes [17,18], juvenile idiopathic arthritis [19], systemic lupus erythematosus [20], hepatitis C-associated mixed cryoclobulinemia vasculitis [21], autoimmune polyglandular syndrome type II [22], and psoriasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…19,20,[22][23][24][25] Whether there is a distinct pattern of Treg cell deviation in T1D patients is still not clear. [35][36][37] In the studies referenced above, the numbers of Treg cells were assessed in the peripheral blood of T1D patients. The discrepancy regarding alterations in the Treg cell numbers in the peripheral circulation of the T1D patients reported in these publications might reflect fluctuations among individuals.…”
Section: Treg Cells In Plns In T1dmentioning
confidence: 99%
“…A large number of studies have shown that Treg cells are major players in autoimmune responses in humans (8)(9)(10) and that they may be affected by immunomodulatory therapy (11,12). We have previously demonstrated that patients with MC vasculitis have a quantitative defect in peripheral blood Treg cells (13) as compared with patients chronically infected with HCV but without autoimmune manifestations.…”
Section: Conclusion the Strong Positive Correlation Between Clinicalmentioning
confidence: 99%